Long non-coding RNAs and control of gene expression in the immune system - Atianand, Maninjay K.; Fitzgerald, Katherine A. (Trends in molecular medicine, 2014)
•The expression of lncRNAs in the immune system is cell type- and context-dependent.•Several lncRNAs identified to date regulate immune gene expression.•LncRNAs play crucial role in host–pathogen interactions.•The majority of disease-associated SNPs lie in regulatory regions of the genome. All cells of the immune system rely on a highly integrated and dynamic gene expression program that is controlled by both transcriptional and post-transcriptional mechanisms. Recently, non-coding RNAs, including long non-coding RNAs (lncRNAs), have emerged as important regulators of gene expression in diverse biological contexts. lncRNAs control gene expression in the nucleus by modulating transcription or via post-transcriptional mechanisms targeting the splicing, stability, or translation of mRNAs. Our knowledge of lncRNA biogenesis, their cell type-specific expression, and their versatile molecular functions is rapidly progressing in all areas of biology. We discuss here these exciting new regulators and highlight an emerging paradigm of lncRNA-mediated control of gene expression in the immune system.